Road Towards Mili Meter Wave Communication For 5G Network: A Technological Overview - Kumar Mohapatra, Sumant; Ranjan Swain, Biswa; Pati, Nibedita; Pradhan, Annapurna (Transactions on Engineering and Computing Sciences, 2014)
For future broadband cellular communication networks wireless carriers has motivated the exploration of the under-utilized millimeter (mm-wave) frequency spectrum. The cellular mm wave propagation is densely populated in the world. It is vital for the design and operation of future fifth generation cellular networks that use the mm-wave spectrum.  This paper provides the overview of the recent world-wide activities for beyond 4G and 5G wireless standardization and technological aspects for millimeter wave communications.  A complete characterization of the mm-wave link for next generation 5G mobile broadband remains elusive. The coverage, directionality and reliability of mm-wave communications will require new innovations in system design and communication technologies that are far from trivial. The transmission range and spatial selectivity’s in the mm-wave bands especially in non line of sight channels can be increased by system design. So it require highly direction antennas and steerable antenna beams to compensate for the high propagation loss.